Benign Calcified Thyroglossal Duct Cyst, – Defying The Hallmark of Papillary Carcinoma, 4th Case Reported In Literature - SN, Al-Yahya; MH, Lye; CP, Loo; MB, Marina (IIUM Medical Journal Malaysia, 2017)
Thyroglossal duct cyst is the most common upper neck midline lesion in children. Approximately 1% of thyroglossal duct cyst undergoes malignant transformation. Calcification which is a marker of malignancy almost always points out to papillary thyroid carcinoma. Benign case of calcified thyroglossal cyst maybe undiagnosed or under reported. We report a case of a 5 year old girl with a benign calcified thyroglossal duct cyst, a fourth case in world literature. Here the differences between a benign and malignant thyroglossal duct cyst are discussed.